The Detection and Sequencing of a Broad-Host-Range Conjugative IncP-1β Plasmid in an Epidemic Strain of Mycobacterium abscessus subsp. bolletii - Leão, Sylvia Cardoso (Public Library of Science, 2013)

(untitled)
BACKGROUND: An extended outbreak of mycobacterial surgical infections occurred in Brazil during 2004–2008. Most infections were caused by a single strain of Mycobacterium abscessus subsp. bolletii, which was characterized by a specific rpoB sequevar and two highly similar pulsed-field gel electrophoresis (PFGE) patterns differentiated by the presence of a ∼50 kb band. The nature of this band was investigated. METHODOLOGY/PRINCIPAL FINDINGS: Genomic sequencing of the prototype outbreak isolate INCQS 00594 using the SOLiD platform demonstrated the presence of a 56,264-bp circular plasmid, designated pMAB01. Identity matrices, genetic distances and phylogeny analyses indicated that pMAB01 belongs to the broad-host-range plasmid subgroup IncP-1β and is highly related to BRA100, pJP4, pAKD33 and pB10. The presence of pMAB01-derived sequences in 41 M. abscessus subsp. bolletii isolates was evaluated using PCR, PFGE and Southern blot hybridization. Sixteen of the 41 isolates showed the presence of the plasmid. The plasmid was visualized as a ∼50-kb band using PFGE and Southern blot hybridization in 12 isolates. The remaining 25 isolates did not exhibit any evidence of this plasmid. The plasmid was successfully transferred to Escherichia coli by conjugation and transformation. Lateral transfer of pMAB01 to the high efficient plasmid transformation strain Mycobacterium smegmatis mc(2)155 could not be demonstrated. CONCLUSIONS/SIGNIFICANCE: The occurrence of a broad-host-range IncP-1β plasmid in mycobacteria is reported for the first time. Thus, genetic exchange could result in the emergence of specific strains that might be better adapted to cause human disease.